Trinca de solidificação off-corner no lingotamento contínuo de Tarugos - Lucas Vieira Penna (2005)
Internal cracks are a major quality problem in the continuous casting of billets. At Belgos plant, located in João Monlevade, off-corner crack is the most common kind of internal crack in steel billets. This type of crack occurs more frequently in medium carbon steels (carbon content between 0.25 and 0.45%). The focus of the present investigation is the identification and analysis of the main factors that affect the formation of off-corner cracks in billets of medium carbon steels. The factors that were considered in the present work were: - type of flux powder; - intensity of secondary cooling; - type and taper of the mold tube; - intensity of the electromagnetic stirring in the mold; - water flux in the mold; - corner radius of the mold tube. By using a statistical tool named DOE (Design of Experiments), experiments were carried out to determine the effect of each one of the factors listed above on the formation of off-corner cracks. Based on the results of these experiments, it was possible to conclude that increasing the water flux in the mold, using a flux powder with low viscosity and increasing the intensity of the electromagnetic stirring the formation of off-corner cracks was minimized.